Current state of value management implementations in Malaysian public projects / Aini Jaapar, Nur Amani Maznan and Mardhiah Zawawi. - Jaapar, Aini; Maznan, Nur Amani; Zawawi, Mardhiah (Universiti Teknologi MARA Cawangan Selangor, 2018)
In Malaysia, Jaapar (2006) stated that Value Management (VM) is still at the early stage of its evolution. Despite its infancy stage, the authorisation of VM Circular 3/2009 by Economic Planning Unit (EPU) has made all public projects exceeding RM50 million to implement the VM studies. There are three objectives to be achieved in this research. The objectives are to identify the VM participants’ receptiveness towards the VM implementation in a workshop environment setting, to observe the VM manual application in the VM workshop and to discover the challenges faced by the VM participants and facilitators.